Epidemiologia e manejo do míldio (Plasmopara viticola) em uva fina de mesa sob cobertura plástica - Genta, Werner (2010)
Grapevine is the third economically more important fruitcrop in Brazil. Downy mildew, caused by the oomycete Plasmopara viticola Berl. & de Toni, is a major disease of grapes in Paraná State, Brazil. This research was conducted aiming to test the hypothesis that plastic cover might reduce downy mildew damages in table grape orchards due to leaf wetness reduction. Thus, the objectives of this research were to study epidemics of downy mildew under raffia plastic cover and under plastic screens shade, and to evaluate the use of raffia plastic cover as tool for downy mildew management in table grapes. The experiments were run in a commercial orchard of 'BRS-Clara' table grape ("CNPUV 154-147' x 'Centennial Seedless'), grafted on the rootstock 'IAC 572 - Jales' and 'IAC 766 - Campinas', in Marialva County, PR - Brazil. The experimental design was randomized block with four replicates. The following treatments were compared: 1. under plastic screens shade without fungicide sprays; 2. under plastic screens shade with fungicide sprays (standard, positive control); 3. under plastic raffia cover without fungicide sprays for downy mildew; 4. under plastic raffia cover with up to 50% reduction of fungicide sprays; 5. under plastic raffia cover with up to 75% reduction of fungicide sprays; 6.under plastic raffia cover with K-phosphyte and cupper sprays; 7. under plastic raffia cover without fungicide sprays. The experiments were run in four harvest seasons: September to December/2007, January to April/2008, September to December/2008 and January to April/2009. In each crop season were conducted two tests. The epidemiology of the disease under plastic screen shade and under plastic raffia was analyzed through linear correlation between severity (temporal progress of disease) and microclimate variables, collected with micremeteorological stations. It was observed significant correlation indexes (P ≥ 0.05) with cumulative hours with relative humidity (RH) greater than 90%, cumulative hours of RH above 90% in the dark, cumulative hours of leaf wetness and cumulative hours of leaf wetness in the dark in all seasons for precipitation. Plastic raffia cover without fungicide sprays reduced downy mildew intensity, however yield was decreased compared with the standard treatment. Plastic cover allowed up to 75% reduction in the number of fungicide sprays needed to control the disease.